The Application of Augmented Reality Media to Improve Cognitive Abilities in Early Childhood - Juliasari, Nurlela; Rohmiati, Rohmiati; Esita, Zulaeni (Research, Training and Philanthropy Institution Natural Aceh, 2025)
The purpose of this study was to determine the effect of applying Augmented Reality media in improving the cognitive abilities of early childhood students at Aisyiyah Bustanul Athfal 1 Kendari Kindergarten. This study employs a quantitative research approach using a pretest-posttest experimental design. The instrument used in this study is an observation assessment sheet using a Likert scale. This study employs total population sampling, so all 16 children in Class B of Aisyiyah Bustanul Athfal 1 Kendari Kindergarten were included as the sample. The data analysis techniques used in this study include: (1) calculating the average change in scores, and (2) the cognitive development index of children. Based on the results of the cognitive development calculation, a percentage of 81.25% was obtained. This indicates a significant improvement in children's cognitive abilities following the use of Augmented Reality (AR) media. The children demonstrated better ability in recognising objects, such as fruits, vegetables, animals, and vehicles, as well as in following instructions given through the AR medium. Moving forward, more schools should consider integrating AR technology into their teaching and learning processes. Additionally, it is crucial to continually enhance the infrastructure and accessibility of AR devices, ensuring that all children can benefit from them.